Ultisol optimization strategy: the use of Tithonia compost and rice husk biochar to improve nodulation and promote soybean (Glycine max (L.) Merril) growth - Lestari, Ardiyaningsih Puji; Zulkarnain, Zukkarnain; Adriani , Adriani; Mapegau, Mapegau; Eliyanti, Eliyanti; Riduan, Ahmad (Brawijaya University, 2024)
This study aimed to investigate the optimization of Ultisol soil using biochar and compost to increase nodule formation and performance of soybeans. The trial was conducted at the Research and Teaching Farm, Faculty of Agriculture, University of Jambi, for six months from April through to October 2021. Three levels of compost (5 t ha-1, 10 t ha-1, and 15 t ha-1) were tested in combination with three levels of biochar (5 t ha-1, 10 t ha-1, and 15 t ha-1). A completely randomized design was employed with three replications. Each experimental unit consisted of 20 plants, and 25% of the population was taken as sample plants. Results indicated that the application of soil ameliorant in the form of Tithonia compost and biochar could increase soil pH and nutrient contents and reduce C/N ratio. Tithonia compost + biochar improved Ultisol productivity as indicated by increased nodule formation and soybean growth. The combination of Tithonia compost and biochar, each of 15 t ha-1, was the best combination for the optimization of Ultisol, which produced the highest biological nitrogen fixation rate and resulted in the best soybean growth.